Human Population Effects on Metal Levels in Worcester, Massachusetts, USA - GOKSEL OZDILEK, HASAN; BULUT, YAKUP (Asian Journal of Chemistry, 2010)
In this study, heavy metal concentrations in catch-basin cleanings and street sweepings in Worcester, Massachusetts, USA were determined. Based on the results, population vs. metal levels were graphed using selected population and metal concentrations in cities situated in the developed countries. It was found that urban population is important for metal levels, specifically cadmium and lead, in streets. However, no effect of city population on street copper was found. Therefore, urban street dust management, specifically in Ihe large urban areas, should be performed carefully due to the fact that metal contaminated street dust causes serious health problems.